Paving the Way to Eureka—Introducing “Dira” as an Experimental Paradigm to Observe the Process of Creative Problem Solving - Loesche, Frank; Goslin, Jeremy; Bugmann, Guido (Frontiers in Psychology, 2018)
‘Dira’ is a novel experimental paradigm to record combinations of behavioural and metacognitive measures for the creative process. This task allows assessing chronological and chronometric aspects of the creative process directly and without a detour through creative products or proxy phenomena. In a study with 124 participants we show that (a.) people spend more time attending to selected versus rejected potential solutions, (b.) there is a clear connection between behavioural patterns and self-reported measures, (c.) the reported intensity of Eureka experiences is a function of interaction time with potential solutions, and (d.) experiences of emerging solutions can happen immediately after engaging with a problem, before participants explore all potential solutions. The conducted study exemplifies how ‘Dira’ can be used as an instrument to narrow down the moment when solutions emerge. We conclude that the ‘Dira’ experiment is paving the way to study the process, as opposed to the product, of creative problem solving.